Comparative results between densified agricultural and woody biomass in fixed bed combustion - Stoica, Dorel; Pisa, Ionel; Pop, Elena; Negreanu, Gabriel; Jarcu, Elena Adriana (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The paper analyses the behaviour of cereal straw briquettes in combustion at energy installations equipped with fixed grates for powers below 75 kW, intended for uses in the field of agriculture. A comparison was made with the combustion of sawdust briquettes. A wider involvement of the energy use of cereal straws, which are in large quantities in certain agricultural regimes, is envisaged. The research includes a new production of cereal straw briquettes from the Oltenia area, previous research being carried out with briquettes made in the agricultural area of North-Eastern Moldova. The use of cereal straw for energy purposes, however, collided with the final processes of combustion when the ash becomes adherent to the elements of the combustion plant, so this new approach will contribute to broadening the knowledge about this biofuel that represents a certain future. The work presented experimental combustion tests comparing the two fuels (cereal straw briquettes and wood sawdust respectively) at a 55 kW pilot plant, plant equipped with a fixed grill.